The effects of functional electrical stimulation cycling on gait parameters in diplegic cerebral palsy: a single-blind randomized controlled trial - Turker, Duygu; Yakut, Yavuz; Yasar, Evren; Kerem Gunel, Mintaze; Yilmaz, Bilge; Tan, Arif Kenan; Yakut, Yavuz (TAYLOR & FRANCIS LTD)
PurposeTo investigate the effects of functional electrical stimulation cycling (FES-C) training in addition to conventional physical therapy on gait, muscle strength, gross motor function, and energy expenditure in ambulatory children with spastic diplegic cerebral palsy.Materials and methodsTwenty children with diplegic cerebral palsy were randomly assigned to FES-C group (n = 10) or control group (n = 10). Subjects trained 3 days/week for 8 weeks. Control group received conventional physical therapy. The FES-C group additionally received FES-C training. The functional muscle test was used for muscle strength assessment. Vicon-3D system was used for gait analysis. Gross Motor Function Measure (GMFM-88) was used for motor function assessment and calorimeter was used for energy expenditure. Measurements were performed at the baseline, at the eight week and at the sixteenth week.ResultsFunctional muscle strength, gross motor function, and energy expenditure improved more in the FES-C group after training and follow up (p < 0.05). There was no significant difference found between the changes in gait parameters of the two groups after treatment and follow up (p > 0.05). Pelvic tilt while walking decreased after training in the FES-C group (p < 0.05).ConclusionsFES-C applied in addition to conventional physical therapy in children with diplegic cerebral palsy is more effective than conventional physical therapy for increasing functional muscle strength, improving gross motor function functions, and reducing energy expenditure.
Keywords: oxygen expenditure; resistance training; electric stimulation therapy; gait analysis; Cerebral palsy